2015
DOI: 10.1007/s00248-015-0661-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Arbuscular Mycorrhizal Fungi in a Brazilian Atlantic Forest Toposequence

Abstract: The diversity of arbuscular mycorrhizal fungi (AMF) was studied in the Atlantic Forest in Serra do Mar Park (SE Brazil), based on seven host plants in relationship to their soil environment, altitude and seasonality. The studied plots along an elevation gradient are located at 80, 600, and 1,000 m. Soil samples (0-20 cm) were collected in four seasons from SE Brazilian winter 2012 to autumn 2013. AMF spores in rhizosperic soils were morphologically classified and chemical, physical and microbiological soil car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
51
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 30 publications
7
51
3
1
Order By: Relevance
“…Similarly, Gigasporaceae fungi were mainly found at 3,300 m and 3,500 m, but unable to be detected above 3,700 m in the Puna mountain grassland in Argentina5 and mainly detected in <3,000 m but not in >4,000 m on the Qinghai-Tibet Plateau6. In addition, although Glomeraceae was dominant in this study as reported in previous studies67848, the species richness of Glomeraceae also declined with increasing altitude6. These findings suggested that members of Gigasporaceae and Glomeraceae prefer to relatively lower elevation compared with the highland.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similarly, Gigasporaceae fungi were mainly found at 3,300 m and 3,500 m, but unable to be detected above 3,700 m in the Puna mountain grassland in Argentina5 and mainly detected in <3,000 m but not in >4,000 m on the Qinghai-Tibet Plateau6. In addition, although Glomeraceae was dominant in this study as reported in previous studies67848, the species richness of Glomeraceae also declined with increasing altitude6. These findings suggested that members of Gigasporaceae and Glomeraceae prefer to relatively lower elevation compared with the highland.…”
Section: Discussionsupporting
confidence: 59%
“…The distinct AM fungal community compositions were also found along altitudinal gradients on the basis of analysis of spore morphology6 and molecular techniques847. Furthermore, we found that the AM fungal community composition was significantly related to soil moisture and plant functional group composition, and was marginally related to soil TOC and available N. Indeed, these plant and soil variables showed substantial difference amongst different original elevations in this study (Supplementary Table S1), which may result in changes in AM fungal composition, as previous studies reported that AM fungal community composition was structured by plant community112449 and soil variables1314152750.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies indicated that araucaria is capable of supporting AMF symbiosis with a greater number of different fungal species [11,[22][23][24][25] than that we found in this experiment. To date, araucaria AMF spore richness varied from 8 [23] to 13 [11] in forests of the State of Rio Grande do Sul and from 26 [24] to 58 [25] in forests of Sao Paulo. The variation in spore AMF richness has been frequently attributed to heterogeneity in soil habitat and to the variable capacity of AMF species to adapt to climate and soil in different regions [10,13].…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, the AMF phylotypes found in the LY‐2 sample site, especially with respect to the most abundant genus, Septoglomus , must have some traits that allow them to adapt to the specific conditions at this site or to survive as highly adapted spores in the soil. Some studies have demonstrated that Septoglomus was found exclusively under extreme conditions of drought and high temperatures (Bonfim et al, ; Symanczik, Chwat, Boller, Wiemken, & Alyahya'Ei, ) and can play an important role in mitigating drought impact on plants (Grümberg, Urcelay, Shroeder, Vargas‐Gil, & Luna, ). Moreover, the difference in the diversity and community composition of AM fungi under the unhealthy trees in LY‐2, particularly the relatively high frequency of Septoglomus (7.53%), compared to sites LY‐1 (0.99%) and LY‐3 (3.67%), which both contained healthy trees, suggested that the host plants in LY‐2 may allocate different (qualitatively and/or quantitatively) carbon resources to their AM fungal partners (Aguilar‐Trigueros, Powell, Anderson, Antonovics, & Rilling, ), such as specific root‐exudate patterns.…”
Section: Discussionmentioning
confidence: 99%